2004
DOI: 10.1111/j.1572-0241.2004.30733.x
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Macrophage Chemoattractant Protein-1 Expression and Macrophage Infiltration in Squamous Cell Carcinoma of the Esophagusa

Abstract: These results suggest that MCP-1 expression and macrophage infiltration is associated with angiogenic promotion in esophageal SCC. MCP-1 expression may be interactively associated with macrophage infiltration in esophageal SCC; MCP-1 may play an important role in tumor angiogenesis through production of angiogenic factors, such as TP, by recruited macrophages in esophageal SCC. Furthermore, CCR-2 expression in vascular endothelial cells may participate partially in angiogenesis. Clinicopathologically, esophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
113
1
3

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(123 citation statements)
references
References 18 publications
6
113
1
3
Order By: Relevance
“…38 Tumour infiltrating macrophages as such can act as promoters of tumour progression, 39 and it has been reported that macrophages in SCCs of oesophagus contribute to a poor prognosis through the secretion of Macrophage Chemoattractant Protein-1. 40 In contrast; the degree of macrophage infiltration was a favourable prognostic sign in lower gastric cancer. 41 Our data do, however, indicate that a high uPARscore in macrophages at the invasive front leads to shorter survival in adenocarcinomas in and near to the lower oesophagus (see Fig.…”
Section: Discussionmentioning
confidence: 94%
“…38 Tumour infiltrating macrophages as such can act as promoters of tumour progression, 39 and it has been reported that macrophages in SCCs of oesophagus contribute to a poor prognosis through the secretion of Macrophage Chemoattractant Protein-1. 40 In contrast; the degree of macrophage infiltration was a favourable prognostic sign in lower gastric cancer. 41 Our data do, however, indicate that a high uPARscore in macrophages at the invasive front leads to shorter survival in adenocarcinomas in and near to the lower oesophagus (see Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, our data are in agreement with data reporting MCP-1 expression in a variety of human tumour cell lines including gastric, 10 ovarian, 45 breast, 9 melanoma, 46 pancreatic 7 and neuroblastoma cancer cell lines. 47 Similarly, in vivo, MCP-1 was expressed by tumour cells of different types including ovarian, 45,48 gastric, 10 pancreatic, 7 oesophageal 16,18 and also breast carcinoma cells. 8,9,17 More particularly in accordance with our results showing a selective expression of MCP-1 in invasive breast tumour cell lines, Valkovic et al 17 have shown that MCP-1 overexpression in tumour breast carcinoma 52,53 prostate cancer cells 54 and bladder cancer cells.…”
Section: Discussionmentioning
confidence: 95%
“…The correlation between MCP-1 expression and a poor prognosis was also demonstrated for the squamous cell carcinoma of the oesophagus. 16 In tumours, MCP-1 is produced both by peritumoral stromal cells and by tumour cells themselves, but an overexpression of MCP-1 in invasive tumour cells has been documented in several human carcinomas including breast, gastric and oesophageal carcinomas. 10,17,18 If the functional implication of MCP-1 in tumour progression is therefore largely documented, the mechanisms regulating MCP-1 expression in tumour cells are still poorly understood.…”
mentioning
confidence: 99%
“…Similarly, increasing tumour-infiltrating lymphocyte count has been linked with decreased risk of death from gastric cancer in one study, but associated with an adverse prognosis in another (Setala et al, 1996;Grogg et al, 2003). Studies relating to oesophageal cancer are equally contradictory (Ma et al, 1999;Koide et al, 2004). In this study, there were no differences in tissue cytokine concentrations (mRNA or protein) between tumours with a chronic inflammatory infiltrate and those without, suggesting that differential tissue IL-1b expression is likely to be tumour-cell derived.…”
Section: Discussionmentioning
confidence: 99%